Influence of directional wave spreading on a WEC device - Ian Masters (International Marine Energy Journal, 2022)
Wave Energy Converter (WEC) performance is generally sensitive to the wave direction. So, it is important to include the effect of multi-directional waves in numerical modelling. A realistic representation of ocean waves should account for wave height and directional spreading parameters specific to the WEC deployment location. A high quality generalised directional distribution is dependent on the wave direction and frequency. Here we compare the power produced, the wave field, and the motion of the WaveSub device for different frequency-directional distribution cases. Directional spreading has been modelled using different model distributions such as the uniform cosine fourth, Mitsuyasu, Hasselman and Donelan-Banner. The hydrodynamic coefficients are computed for all wave directions using Nemoh. Then, the WEC-Sim code has been extended to add the capability to simulate different user selected frequency-directional spreading. The excitation force applied to each hydrodynamic body is updated to account for the effect of the directional spectrum. Results show that power produced is generally 10-20% lower than a single direction case. The motion of the device demonstrates the introduction of sway, roll, and yaw for the directional spreading simulations while the resultant wavefield is more uniform compared to the non-directional case. Computational time is significantly lower than comparable CFD approaches and this makes this method particularly effective.